Effect of carburizing and nitriding duplex treatment on the friction and wear properties of 20CrNi2Mo steel. (1st March 2023) - Chen, Jian; Li, Shaolong; Liang, Yilong; Tian, Xiangyu; Gu, Jiabao
Abstract: In this study, the responses of 20CrNi2Mo steel to carburizing (C) and carburizing-nitriding (C + N) duplex treatment and the effects of these treatments on the friction and wear properties were systematically studied. The 20CrNi2Mo surface layers were characterized by optical microscopy (OM), laser scanning confocal microscopy (LSCM), x-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), Vickers microhardness tests and high-speed reciprocating friction and wear testing. The results showed that after the carburizing and nitriding duplex treatment, an approximately 5 μ m thick compound layer (CL) consisting of the γ ′-Fe4 N and ε -Fe2-3 N phases had formed on the surface, and the diffusion layer depth was approximately 220 μ m. The carbides (MC) stored during carburizing were easily converted to nitrides (MN) during the nitriding process. Furthermore, the surface microhardness (879 HV) was increased by a factor of 2 compared with the substrate (420 HV), the surface residual compressive stress (−652 MPa) was increased significantly, and the surface roughness also increased. Wear analyses under different loads showed that specimen C exhibited the worst wear resistance, and its wear mechanism was mainly abrasive wear. The C + N with CL samples showed excellent wear resistance under a 20-N load; after removing the CL samples (C + N with CL), they showed excellent wear resistance under a 40-N load, and the wear mechanism was mainly adhesive wear. This work showed that the wear resistance was improved significantly by the carburizing and nitriding duplex treatment, but the CL had different effects on the wear performance under different loads.